2020
DOI: 10.1128/mbio.00650-20
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Regulation of Formate Dehydrogenase during CO 2 Fixation in Gas-Fermenting Bacteria

Abstract: Protein lysine acetylation, a prevalent posttranslational modification, regulates numerous crucial biological processes in cells. Nevertheless, how lysine acetylation interacts with other types of regulation to coordinate metabolism remains largely unknown owing to the complexity of the process. Here, using a representative gas-fermenting bacterium, Clostridium ljungdahlii, we revealed a novel regulatory mechanism that employs both the lysine acetylation and transcriptional regulation systems to interactively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 41 publications
(61 reference statements)
0
29
0
1
Order By: Relevance
“…In view of that biotin synthesis is a high energy‐consuming process in cells (Feng et al ., 2013), such a BirA‐mediated feedback regulation on biotin synthesis may be crucial for the control of energy expenditure in bacteria. Theoretically, this regulatory mechanism is especially important for gas‐fermenting clostridia because the carbon fixation and assimilation in these autotrophic bacteria are a net energy consumption process (Zhang et al., 2020a,2020b), and excessive energy consumption in biotin synthesis will cause metabolic burden. But interestingly, a modified Cl BirA with only enzymatically active domain led to a better performance of C. ljungdahlii in gas fermentation (Figs 6 and 8), indicating that an uncontrolled overproduction of biotin is not the key point for the autotrophic growth of C. ljungdahlii .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of that biotin synthesis is a high energy‐consuming process in cells (Feng et al ., 2013), such a BirA‐mediated feedback regulation on biotin synthesis may be crucial for the control of energy expenditure in bacteria. Theoretically, this regulatory mechanism is especially important for gas‐fermenting clostridia because the carbon fixation and assimilation in these autotrophic bacteria are a net energy consumption process (Zhang et al., 2020a,2020b), and excessive energy consumption in biotin synthesis will cause metabolic burden. But interestingly, a modified Cl BirA with only enzymatically active domain led to a better performance of C. ljungdahlii in gas fermentation (Figs 6 and 8), indicating that an uncontrolled overproduction of biotin is not the key point for the autotrophic growth of C. ljungdahlii .…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, this aspect remains minimally explored due to the challenges in genetic tools. Specific to transcriptional regulators (TFs), to our knowledge, only a global regulator CcpA and a TetR‐family regulator (CAETHG_0459) have been identified and characterized in these autotrophic bacteria (Lemgruber et al ., 2019; Zhang et al., 2020a,2020b). CcpA was found to directly regulate the expression of some WLP genes in Clostridium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…increased, possibly because some Clostridium spp. are autotrophic acetogenic bacteria that can produce important chemicals and fuels by using CO 2 ( Zhang L. et al, 2020 ). Lachnoclostridium , a newly defined genus under the highly polyphyletic class Clostridia , showed a decreased relative abundance after pyroligneous acid treatment, consistent with that in CO 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Protein Lysine acetylation (PLA) is known to be a crucial metabolic regulatory mechanism in both prokaryotic and eukaryotic cells, in which multiple PLA-regulated physiological and metabolic processes have been revealed ( 12 , 13 , 14 ). In a previous study on Clostridium ljungdahlii , a representative autotrophic acetogen, we revealed an interactive regulation module that uses both the global transcriptional factor CcpA and acetylation/deacetylation system At2/Dat1 to control carbon fixation ( 15 ). This finding suggested that, in addition to TFs, PLA plays an important role in regulating crucial cellular functions in autotrophic acetogens, leading to the regulation on several levels involving multiple factors.…”
mentioning
confidence: 99%